Searle’s Defence of Internalism - Koťátko, Petr (Organon F, 2012)
The paper argues in favour of the Searlean internalist way of construing the content of thoughts and communicative acts. As interpreted by the author, it reflects the participation of external factors in the determination of content (stressed by externalists like Burge, Putnam, Kripke and Davidson) but it does so in a way which enables to approach the thinking and communicating individual as a real subject of his acts. The crucial move is to incorporate the individual’s reliance on the relevant parameters of his physical or social environment into the construal of the content itself. Then the external factors can be treated as exploited by the individual himself in the articulation of his acts, rather than as intervening into the content through the gaps marked by indexicals, proper names, natural kind terms or concepts borrowed from the communal repertoire. In particular with respect to the last factor the author proposes a maxim of interpretation which he labels as The principle of maximization of subjectivity and regards as a pendant of the well-known Principle of charity.
Keywords: division of linguistic labour; indexicals; internalism/externalism; natural kind terms; proper names; propositional content